Structural Design of a Semiautomatic Position Laser Therapy Equipment - Felix Torre, Maria Fernanda (2025)
In the field of health, innovation is positioned as a key element in the development of effective solutions to treat injuries in various areas of the body. The growing need for advanced biomedical equipment capable of addressing these demands is recognized. In this context, the purpose of this article is the design of a semi-automatic laser therapy equipment, a technique whose benefits for rehabilitation have been widely demonstrated. For the research design, a fusion of the VDI 2206 plus MIT methodologies was carried out. The main objective of this article is to design a semi-automatic laser therapy equipment for rehabilitation with parameter regulation. This article seeks to contribute to the innovation and development of biomedical technology, offering solutions adapted to the required needs. Likewise, it is expected that this design and methodological approach can be used as a reference for future semi-automation projects for the development of biomedical equipment. The result of this research is equipment that can be configured for various treatments depending on the injury, this is achieved through the use of programming and structural position control through inverse kinematics.